Implementation of a second victim program in the neonatal intensive care unit: An interim analysis of employee satisfaction. Issue 6 (December 2018) - Merandi, Jenna; Winning, Adrien M; Liao, Nancy; Rogers, Erin; Lewe, Dorcas; Gerhardt, Cynthia A
Background: While research has established the negative impact of medical errors or adverse events on healthcare providers, few organizations have evaluated support programs for second victims. Thus, we examined satisfaction with a peer support program to provide lessons learned from early implementation. Methods: Participants ( N = 466) were recruited from seven neonatal intensive care units affiliated with a large, pediatric hospital. Following implementation of a peer support program, a mixed-method online survey assessed program satisfaction at 12 month follow-up ( n = 250, 54%). Results: Most participants were female ( n = 243, 97%), white ( n = 239, 96%), and nurses ( n = 180, 72%), with an average age of 40.80 (SD = 11.89) years. Ninety-three (37%) participants observed or were directly involved in an error or adverse event during the preceding six months. Thirty-six (14%) received support from someone within the neonatal intensive care unit, and 16 (16%) had spoken with a peer supporter after the event. All users reported benefit from the interaction. However, most participants were unaware of the program or had not utilized it. Conclusion: Findings suggested that peer support programs are likely to be viewed favorably by second victims. Healthcare providers who accessed the program felt it was a valuable resource and helped them return to work effectively after an error or adverse event. Better communication is needed during early implementation of any peer support program to increase awareness and use of this resource among healthcare providers.